Biofilm Formation in Reverse Osmosis Water at Hemodialysis Units in Two Hospitals Bandung - Aswin Yeoh Kit Shawn; Sunarjati Sudigdoadi; Diah Dhianawaty (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Bacteria in aquatic environments do not usually live as a single free-swimming microscopic cell, but rather as communities of microorganisms that are attached to a surface in the form of biofilm. Biofilm is a major cause of concern to the medical world, as it protects the bacteria from a harsh environment, the host immune system, antimicrobial therapy, and even disinfectant. The aim of this study was to determine which genus or species of bacteria in reverse osmosis (RO) water was able to form a biofilm.Methods: Water samples were taken from RO water of water treatment in hemodialysis (HD) centers at two hospitals in Bandung; at each point of the water treatment plant, bacteria were cultured. Any growth of bacteria was tested with a tube method to determine the formation of biofilm.Results: Micrococcus luteus, Citrobacter diversus, Enterobacter aerogenes, Pseudomonas sp., Serratia sp., Acinetobacter sp. were able to form biofilm while Klebsiella pneumoniae and Staphylococcus saprophyticus were not.Conclusions: Most bacteria isolated from RO water can form a biofilm, and a few are not. This study is successfully to check the possibility of biofilm formation of RO water, therefore, disinfecting RO water regularly is important and highly encouraged.